Impact of Physical Abuse on Internalizing Behavior Across Generations - Esteves, Kyle (J Child Fam Stud, 2017)
This study investigated the multigenerational impact of mothers’ own exposure to physical maltreatment on internalizing symptoms in her child after accounting for her parenting practices, depression, and the child’s own exposure to stressful life events. Children (n = 101, ages 5–16), predominantly African American, were recruited into this cross sectional study using ethnographic mapping and targeted sampling for high-risk neighborhoods. Mothers reported retrospectively on their own exposure to physical maltreatment in childhood, their parenting practices, as well as current depressive symptoms. Maternal report of her child’s exposure to stressful life events and child behavior was also collected. Maternal childhood exposure to physical maltreatment was significantly associated with her child’s internalizing symptoms (p = .004); this effect remained after accounting for child sex, maternal depressive symptoms, harsh parenting practices, and the child’s own exposure to stressful life events. Formal tests of mediation through these pathways were non-significant. Findings suggest mothers’ experience of childhood maltreatment contributes uniquely to children’s internalizing symptoms, potentially through previously uncharacterized pathways. Examination of additional behavioral, psychosocial and biological pathways may help better describe the multi-generational effects of child maltreatment.